Sosialisasi Perilaku Hidup Bersih dan Sehat (PHBS) Di SDS Islam “Plus” Al Manshur Banjarbaru - Hilda Irianty; Ridha Hayati; Deni Suryanto (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
PHBS at school is a set of behaviors practiced by students, teachers and the school community on the basis of awareness as a learning outcome, so that they are able to independently prevent disease, improve their health, and play an active role in creating a healthy environment. The targets and outputs of this service are scientific publications in ISSN journals, publications on social media and the application of PHBS in schools. The method of implementing these activities is to use lecture, discussion and question and answer methods. The implementation of this service was carried out at SDS Islam Al Manshur Banjarbaru with 70 students and 2 homeroom teachers. The stages of this activity are carried out through 3 stages namely the first stage of preparation, the second stage of implementation and the third stage of evaluation. The conclusion obtained after counseling 90% of students understand about Clean & Healthy Behavior.